Influence of HRT on cardiovascular diseases – review of literature - Surkont, Grzegorz; Wlazłowski, Ryszard; Wlaźlak, Edyta; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2006)
In the article authors discuss the influence of HRT (hormonal replacement therapy) and ERT (estrogen replacement therapy) on frequency of cardiovascular events. There are controversies between conclusions from studies: observational and prospective, clinical (ERA, HERS, WHI). It may be caused by differences in women’s populations which were included into analysis in these studies. It is probable that important factors which have influence on effect of used therapy are: time from menopause and progression of atherosclerosis. There may be also big clinical differences between doses, routes of administration and types of hormones. Results of laboratory tests suggest that transdermal therapy, in comparison with oral route, may give better results concerning cardiovascular events. These facts need to be determined in prospective, randomized clinical studies. Because the situation concerning influence of HRT and ERT on cardiovascular diseases is not clear, during individual therapeutic decisions potential benefits and risks must be taken into account. This includes moment of beginning of the therapy, route of administration, doses and types of hormones. Early beginning of the therapy may have positive influence on lower incidence of cardiovascular events. Late first administration of hormones may lead to higher risk of complications. Although we do not have evident clinical proof which show higher safety of transdermal forms, these forms should be seen as first-choice in all women with indications to HRT and ERT.